The development of a competency framework for transanal irrigation. (2nd April 2022) - Henderson, Michelle; Embleton, Rebecca; Wood, Lisa; Conway, Roseanna
Abstract : Transanal irrigation (TAI) is an established treatment in the management of all types of bowel dysfunction. The National Institute for Health Care and Excellence (NICE) recommends that TAI is initiated by a suitably trained health professional; however, it must then be established how that health professional becomes suitably trained. Much has been published about how TAI works, including its benefits and risks and the types of equipment available. However, no definitive competencies have been agreed among experts in this area. The Northern Region Irrigation Professional Group have recently developed a framework of evidence-based competencies for transanal irrigation. This article discusses the process of development and describes the evidence base and benefits behind the competencies.